2018
DOI: 10.1007/s00405-017-4860-9
|View full text |Cite
|
Sign up to set email alerts
|

Satisfaction in rhinoplasty: the possible impact of anxiety and functional outcome

Abstract: Patient satisfaction is preferential in rhinoplasty. In our patient series, patient satisfaction was shown to be correlated with functional outcome but not with surgeon satisfaction. Anxiety was not found to have a significant impact on results of rhinoplasty. Our results should be interpreted cautiously keeping in mind that our patients' primary drive for rhinoplasty was functional.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
15
0
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 15 publications
1
15
0
4
Order By: Relevance
“…21 Despite these findings, Koybasi et al found that preoperative anxiety has no influence on patients' satisfaction after rhinoplasty. 22 Arima et al 23 demonstrated that individuals younger than 30 years had significantly worse satisfaction following rhinoplasty than those aged 30 to 50 years. Despite these factors, AlHarethy et al 24 demonstrated that age and gender do not influence an individual's satisfaction following rhinoplasty.…”
Section: Resultsmentioning
confidence: 99%
“…21 Despite these findings, Koybasi et al found that preoperative anxiety has no influence on patients' satisfaction after rhinoplasty. 22 Arima et al 23 demonstrated that individuals younger than 30 years had significantly worse satisfaction following rhinoplasty than those aged 30 to 50 years. Despite these factors, AlHarethy et al 24 demonstrated that age and gender do not influence an individual's satisfaction following rhinoplasty.…”
Section: Resultsmentioning
confidence: 99%
“…Rhinoplasty (RP) is among the most commonly performed surgeries for both aesthetic and functional purposes (1). Most studies of RP have focused on the surgical technique, level of surgeon experience, development of complications, and revision rate (2,3) However, an assessment of RP from the patient’s perspective, in terms of satisfaction and quality of life, is equally important because these are the predominant factors indicating the success of RP, as well as its ultimate purpose (4,5).…”
mentioning
confidence: 99%
“…Within the constraints of the database, we were unable to determine the indication for cartilage grafting, and this variable could represent a wide variety of tip strut, onlay, alar, dorsal, or spreader grafts. However, prior studies have shown similar results, with patient reported outcome measures improving if the rhinoplasty procedure contained functional components or resulted in aesthetically pleasing nasal architecture 10‐12 . For example, Koybasi et al showed that nasal functional improvement as determined by the Rhinoplasty Outcomes Evaluate scale leads to improved patient satisfaction, and Neaman et al demonstrated that addressing preoperative tip deformities reduces revision rhinoplasty rates 12,13 .…”
Section: Discussionmentioning
confidence: 89%
“…However, prior studies have shown similar results, with patient reported outcome measures improving if the rhinoplasty procedure contained functional components or resulted in aesthetically pleasing nasal architecture [10][11][12]. For example, Koybasi et al showed that nasal functional improvement as determined by the Rhinoplasty Outcomes Evaluate scale leads to improved patient satisfaction, and Neaman…”
mentioning
confidence: 86%